Green Banking Concepts in Qur'an Review - M Zainal Arifin; Muhammad Noor Sayuti; Tiara Septa Ayu; Ali Sadikin (International Journal of Nusantara Islam, 2020)
This study aims to describe the concept of Green Banking in the review of the Qur'an through the approach of Ijmali and Maudhu's interpretation method as its analysis knife. Content analysis is carried out on the verses that are specifically chosen on the basis of their association with the term fasad in the category of environmental damage namely Surah Al-Baqarah [2]: 205 and Surah Ar-Rum [30]: 41. This is because the beginning of the concept of green banking emerged due to environmental damage ,. The research findings revealed from the two verses that it was found that the meaning of damage meant in essence was natural damage (both physical and non-physical) due to anthropogenic factors. Islamic banking in the provision of financing must prioritize projects that are pro-environment and pay attention to aspects of sustainability, both economic, socio-cultural environment or known as Triple P (People, Planet and Profit) with the principles of fairness, balance, benefit, economical and avoid the tyranny.